Informe COSO en las cuentas por cobrar de la escuela de posgrado de la Universidad Nacional de Trujillo, año 2018 - Aponte García, Oscar Juan Peter (2021)
The purpose of this research work is to make an internal control analysis based on the COSO III Report to the accounts receivable of the Graduate School at the National University of Trujillo, year 2018, in order to improve economic management- financial institution of the School, and thus achieve the fulfillment of its objectives, institutional goals and obtain academic excellence, for the benefit of students in the master's and doctoral programs. The research work is of a basic and descriptive type, it belongs to a non-experimental design, since none of the variables, both independent and dependent, will be manipulated. It was carried out through the descriptive, deductive, inductive and analytical-synthetic method, in the development it was possible to apply the questionnaire in order to obtain information on the situation of Internal Control and accounts receivable. This research is made up of a population whose unit of study or finite universe is the administrative staff of the Graduate School of the National University of Trujillo, district of Trujillo, province of Trujillo, region of La Libertad. At the end of the investigation, it was concluded that Internal Control will have a significant impact on the collection of accounts receivable from the Graduate School of the National University of Trujillo in 2018, establishing that both variables have a relationship, since it could be evidenced that the system of Internal Control does have a favorable impact on the recovery of accounts receivable.